Analisis Manajemen Risiko Pelaku UMKM Terhadap Kenaikan Harga Bahan Pokok Di Kota Rengat - Yogi Mey Shaputra; Maryam Monika Rangkuti (CV. Aksara Global Akademia, 2024)
The increase in prices of basic commodities poses a big challenge for Micro, Small, and Medium Enterprises (MSMEs) in Rengat City. This price increase can impact the sustainability of MSMEs and pose significant financial risks. This research aims to analyze how MSMEs in Rengat City manage the risks arising from the increase in prices of basic commodities in 2023. The research methodology includes observation, interviews, and statistical data analysis. The research results show that effective risk management helps MSMEs reduce the negative impact of rising prices of basic commodities. This research also provides recommendations for improving risk management in MSMEs and supporting the growth of the MSME sector in Rengat City.